Combustion Studies of a Non-Road Diesel Engine with Several Alternative Liquid Fuels - Hissa, Michaela; Niemi, Seppo; Sirviö, Katriina; Niemi, Antti; Ovaska, Teemu (Molecular Diversity Preservation International (MDPI), 2019)
Sustainable liquid fuels will be needed for decades to fulfil the world’s growing energy demands. Combustion systems must be able to operate with a variety of renewable and sustainable fuels. This study focused on how the use of various alternative fuels affects combustion, especially in-cylinder combustion. The study investigated light fuel oil (LFO) and six alternative liquid fuels in a high-speed, compression-ignition (CI) engine to understand their combustion properties. The fuels were LFO (baseline), marine gas oil (MGO), kerosene, rapeseed methyl ester (RME), renewable diesel (HVO), renewable wood-based naphtha and its blend with LFO. The heat release rate (HRR), mass fraction burned (MFB) and combustion duration (CD) were determined at an intermediate speed at three loads. The combustion parameters seemed to be very similar with all studied fuels. The HRR curve was slightly delayed with RME at the highest load. The combustion duration of neat naphtha decreased compared to LFO as the engine load was reduced. The MFB values of 50% and 90% occurred earlier with neat renewable naphtha than with other fuels. It was concluded that with the exception of renewable naphtha, all investigated alternative fuels can be used in the non-road engine without modifications.
Keywords: alternative fuels; CI engines; combustion duration; heat release rate; in-cylinder combustion; fi=Energiatekniikka|en=Energy Technology|